The simplified guide to not-for-profit accounting, formation and reporting - Scot, Laurence (Hoboken, N.J. : John Wiley & Sons, 2010)
A complete and easy to understand guide to the fundamentals of how not-for-profit organizations are formed and run, as well as their structure and the unique accounting and reporting issues they face. Providing you with a comprehensive understanding of how to maintain the "books" of a typical nonprofit entity and comply with numerous reporting requirements, The Simplified Guide to Not-for-Profit Accounting, Formation & Reporting equips you with everything you need to know to form a Not-For-Profit, setup an accounting system, record financial transactions and report to donors and reg.
Introduction -- NFP organization formation -- NFP organizational structure -- Introduction to NFP accounting and reporting -- NFP accounting system and financial statements -- Assets-concepts and data flow -- Liabilities and net assets--concepts and data flow -- Accounting for support and revenue -- Accounting for personnel costs and other expenses -- Investments, pooling and split-interest agreements -- Subsidiaries and interrelated entities -- Budget development and applications -- Special types of NFP organizations -- Regulatory reporting (990, 990-T, and 990-PF) -- Contribution/grant applications and reporting -- Audits--preparation and response -- Conclusion.
Print version record.
John Wiley and Sons
Keywords: Nonprofit organizations -- Accounting; Nonprofit organizations -- Finance; Associations sans but lucratif; Associations sans but lucratif -- Finances; BUSINESS & ECONOMICS -- Accounting -- Financial; Nonprofit organizations -- Accounting; Nonprofit organizations -- Finance